THE EFFECT OF MIND MAPPING METHOD TO THE LEARNING ACTIVITIES OF VII CLASS STUDENT IN SCIENCE - Dini Afriansyah; Muhammad Isnaini; Erie Agusta; Delta Amelia (Al 'Ilmi : Jurnal Pendidikan MIPA, 2017)
This research aims to know the influence of method of Mind Mapping to learning activities of students on classification of living things material in VII Class at one of Junior High School in Palembang. Research methods used in this research is a Quasi Experimental Design. The population in this research is the whole students in VII class of Junior High School that consist of 2 classes numbered 64 students. Sampling that used is purposive sampling technique. The sample of this research is VII.1 class with 32 students as experiment class and VII.2 class with 32 students as a control class. On the process of learning, experimental class taught by using Mind Mapping method and the control class by using the conventional methods (discussion group). Data collection is using the observation sheet of student learning activities that have been tested using the formula of Aiken's v. The results of this study showed that the average student learning activities on the experimental class in 2 meetings i.e. 79, 2% of students who have been active with very active category. On the control class that the percentage of liveliness is 73,90% students with active category. The results of data analysis is using t-test with significant level 0,05 obtained tarithmetic = 3,775 while ttable = 1,671 so tarithmetic > ttable. Therefore Ha is received and H0 is rejected. It can be inferred that Mind Mapping methods can affect tostudent learning activities. Keywords: classification of livings learning activity, mind mapping, science